Tatit, Meschonnic and the translation of Caipira (Marques; Macaraí 1992): initial dialogues and challenges - Santos, Julio César Ribeiro dos (TradTerm, 2021)
In light of the initial dialogue between Semiotics of Song (Tatit 2003; 2012) and Translation Studies (Jakobson 2010; Meschonnic 2006; 2008), I propose the description and analysis of some text elements of the song Caipira (Marques 1992) present in the album Planeta Azul (Chitãozinho & Xororó 1992) and its integral translation of Grandes clássicos da música sertaneja vol. I (Chitãozinho & Xororó 2007). I seek to emphasize the interdependence between analytical categories historically and epistemologically treated by linguists in the order of their discretion and careful that, while elementary structural aspects such as lyrics, melody and harmony are preserved, the Rhythm, condition of subjective and corporeal organization of the discourse and apprehended in the order of the continuum between the levels (Meschonnic 2006), it allows the production and recognition of different subjectivities and historicities.